Functional analysis and treatment of problem behavior related to mands for rearrangement. Issue 1 (10th January 2018) - Torres‐Viso, Mariana; Strohmeier, Craig W.; Zarcone, Jennifer R.
Abstract : This study is a systematic replication of a functional analysis (FA) of the relation between mands and problem behavior. We extended treatment approaches for this problem behavior function, and describe the treatment of problem behavior related to mands for rearrangement demonstrated by a 12‐year‐old girl with autism spectrum disorder and Smith‐Magenis syndrome. The mands consisted of requests for others to change their body positioning or proximity, or rearrange items back to their original position. An FA confirmed the relation between problem behavior and mand compliance, and functional communication training with extinction decreased problem behavior and increased functional communication responses. Problem behavior remained low as gradually longer nonreinforcement periods were introduced using a multiple schedule.